2020
DOI: 10.21927/jnki.2020.8(2).87-94
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Parents’ Parenting And Independence Level Of Activity Daily Living (ADL) In Soft Mental Retardation Children

Abstract: <p><em>ABSTRACT</em></p><p><em>Introduction: Mental retardation children are children who have a lack of intelligence from the time of their development. Parenting is very influential on the independence of children with mild mental retardation because good parenting from parents will help mild mental retarded children to fulfill their activity daily living needs (ADL) independently. The purpose of this study was to determine the relationship of parenting parents with an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…The results showed that there was a significant relationship between parenting and handwashing behavior, which means that the better the parenting applied by the parents with good guidance and direction, the better the handwashing behavior of intellectual disability children in Special School 2 Banjarmasin. It is expected that parents apply appropriate parenting styles to their children and encourages them to explore their potential and abilities by providing many positive activities so that children can learn independently, especially in activities of daily life such as washing hands (Jayanti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that there was a significant relationship between parenting and handwashing behavior, which means that the better the parenting applied by the parents with good guidance and direction, the better the handwashing behavior of intellectual disability children in Special School 2 Banjarmasin. It is expected that parents apply appropriate parenting styles to their children and encourages them to explore their potential and abilities by providing many positive activities so that children can learn independently, especially in activities of daily life such as washing hands (Jayanti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pola asuh dan peran keluarga dianggap sebagai faktor determinan yang mempengaruhi perkembangan kemandirian dalam Aktivitas Kehidupan Sehari-hari seperti kebersihan diri, eliminasi, makan, minum, dan berpakaian (Dwi Jayanti et al, 2020). Anak yang mengalami disabilitas intelektual sangat memerlukan dukungan khusus dari keluarga, karena dukungan tersebut akan mempengaruhi sikap dan perilaku anak, dukungan keluarga sangat penting karena keluargalah yang paling lama berinteraksi dengan pasien.…”
Section: Pendahuluanunclassified